Low Temperature Influence on Activity in Alginate Microcapsules Incorporated-Enzymes - Khala, Iryna; Rozanova, Kateryna; Repina, Svitlana; Nardid, Oleg (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4): 263–267